The effect of fatigue on spike jump biomechanics in view of patellar tendon loading in volleyball - Vermeulen, S.; De Bleecker, C.; Spanhove, V.; Segers, V.; Willems, T.; Roosen, P.; Vanrenterghem, J.; De Ridder, R. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background and Objective Patellar tendinopathy (PT) is a highly prevalent overuse injury in volleyball and is often linked with overloading of the patellar tendon. Little is known, however, about whether and how patellar tendon loading is affected by fatigue during the most challenging jump activity in volleyball. Therefore, this study investigates the effect of a high-intensity, intermittent fatigue protocol on movement alterations in terms of patellar tendon loading during a volleyball spike jump.